HUBUNGAN PERAN PENGAWAS MENELAN OBAT (PMO) DENGAN KEBERHASILAN MINUM OBAT PASIENTUBERKULOSIS PARU DI WILAYAH KERJA PUSKESMAS ULAK TANO KAB. PADANG LAWAS UTARA - Mastiur Napitupulu (Program Studi Ilmu Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Indonesia Timur, 2020)
Tuberculosis (TB) is an important health problem now. The number of new TB ccase in indonesia was 420.994 cases in 2017. The purpose of this study was to determine the relationship between the role of the Superintendent of Swallowing Drugs (PMO) with the Success of Taking Drugs for Lung Tuberculosis Patients. The study design used correlational research with a sample of 40 pulmonary TB patients and the sampling technique was total sampling. This research was conducted in August 2109 until February 2020. Measuring instruments using a questionnaire sheet Then tested with the chi-square test with an alternative that is the fisher test. The results of this study indicate the P-value = 0,000 <0.05 there is a significant relationship between PMO and the success of taking TB patient medication. There is a significant relationship between the role of PMO on the success of TB treatment at the Ulak Tano Health Center and the community can understand the role of PMO for pulmonary TB sufferers.